Evaluation of Kawasaki Disease Risk-Scoring Systems for Intravenous Immunoglobulin Resistance - Sleeper, Lynn A.; Minich, L. LuAnn; McCrindle, Brian M.; Li, Jennifer S.; Mason, Wilbert; Colan, Steven D.; Atz, Andrew M.; Printz, Beth F.; Baker, Annette; Vetter, Victoria L.; Newburger, Jane W. (The Journal of pediatrics, 2011)
To assess the performance of 3 risk scores from Japan that were developed to predict, in children with Kawasaki disease, resistance to intravenous immunoglobulin (IVIG) treatment. We used data from a randomized trial of pulsed steroids for primary treatment of Kawasaki disease to assess operating characteristics of the 3 risk scores, and we examined whether steroid therapy lowers the risk of coronary artery abnormalities in patients prospectively classified as IVIG resistant. For comparability with published cohorts, we analyzed the data of 99 patients who were not treated with steroids (16% IVIG-retreated) and identified male sex, lower albumin level, and higher aspartate aminotransferase level as independent risk factors for IVIG resistance. The Kobayashi score was similar in IVIG-resistant and -responsive patients, yielding a sensitivity of 33% and specificity of 87%. There was no interaction of high-risk versus low-risk status by treatment received (steroid versus placebo) with any of the 3 risk score algorithms. Risk-scoring systems from Japan have good specificity but low sensitivity for predicting IVIG resistance in a North American cohort. Primary steroid therapy did not improve coronary outcomes in patients prospectively classified as being at high-risk for IVIG resistance.